ANALISIS PERLAKUAN AKUNTANSI DAN PELAPORAN HIBAH PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SULAWESI UTARA - Abdul, Sri Devi; Alexander, Stanly; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2018)
A grant is a form of assistance that does not have to be returned and does not bind a given party to a specific commitment. The provision of money, goods or services must be viewed long-term impact and should still pay attention to the independence of the nation and the independence of the government. Governments may also provide grants to governments of other countries, international organizations, local governments, enterprises, institutions or communities for the purpose of humanitarian solidarity, welfare improvement and other economic and social objectives. Grant giving must be done by taking into account aspects of needs, and justice. This study aims to determine the accounting treatment of grants and grant reporting at the Regional Office of the Ministry of Religious Affairs of North Sulawesi Province The research method used in this thesis research is descriptive method whose purpose each data collected analyzed then drawn a conclusion and type of research used is qualitative descriptive. The results obtained that the accounting treatment of grants at the Regional Office of the Ministry of Religious Affairs of North Sulawesi Province has been accrual based and reporting is in accordance with Governmental Accounting Standards Technical Bulletin number 13 which regulates the accounting and reporting of Ministries / Institutions.Keywords: Analysis, Accounting Treatment, Grants